Integrating depth and rigor in ethnobiological and ethnomedical research - Ulysses Paulino Albuquerque; Romulo Romeu da Nóbrega Alves (BMC, 2024)
Abstract Ethnobiology and ethnomedicine, traditionally descriptive disciplines chronicling Indigenous People and Local Community (IPLC) practices, face the challenge of incorporating hypothesis-driven research to address contemporary issues. This paper argues for a synergistic approach where both approaches are valued for their unique contributions to understanding human-nature interactions and informing policy.